An association between PLA2G6 and PLA2G4C gene polymorphisms and schizophrenia risk and illness severity in a Croatian population. (June 2017) - Nadalin, Sergej; Buretić-Tomljanović, Alena
Abstract: We investigated the allele and genotype frequency of the rs4375 and rs1549637 polymorphisms in phospholipase A2 (PLA2)G6 and PLA2G4C genes in 203 patients with schizophrenia and 191 controls in a Croatian population. We hypothesized that these polymorphic variations might influence the age of schizophrenia onset and Positive and Negative Syndrome Scale psychopathology (PANSS) data. We detected a significant overrepresentation of the PLA2G6-CT and PLA2G4C-AT genotype combination in patients compared with controls (14.7% vs. 7.3%, P < 0.05). The combined PLA2G6/PLA2G4C heterozygosity was associated with about a two-fold higher schizophrenia risk. We found no significant influence of the PLA2G6 and PLA2G4C polymorphisms on mean age at first hospital admission (P > 0.05) and that the investigated polymorphisms significantly influenced the clinical psychopathology only in male patients. The PLA2G4C polymorphism accounted for approximately 12% of negative symptom severity; whereas, the PLA2G6/PLA2G4C interaction contributed to a similar extent to total PANSS symptom variations. Highlights: We investigated the role of PLA2G6 and PLA2G4C gene polymorphisms in schizophrenia. The investigated polymorphisms alone do not contribute to schizophrenia risk/onset. The interaction between the polymorphisms contributes to schizophrenia risk. The PLA2G4C polymorphism alone influences psychopathology data in males. The PLA2G6/PLA2G4C interaction also influences psychopathology data in males.